2011
DOI: 10.1128/jvi.01647-10
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of HeLa Cells Is a Conserved Feature of High-Risk Human Papillomavirus E8^E2C Proteins and Can Also Be Achieved by an Artificial Repressor Protein

Abstract: Infections with certain human papillomaviruses (HPV), such as type 16 (HPV16), 18, or 31, are a necessary risk factor for the development of cervical cancer. Transcript analyses of several HPV revealed that the viral E2 gene encodes both the E2 regulator protein and the E8^E2C protein, which differ in their amino termini. Up to now, functional studies have focused on HPV31 E8^E2C and demonstrated that it is a potent repressor of viral transcription and replication. However, recent analyses of HPV16 genomes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…This experiment was repeated three times with similar outcomes. These findings are similar to the effects reported by the reduction of E6 and E7 transcript levels in cervical cancer cell lines by siRNA or expression of E2 or E8^E2C proteins (18,(37)(38)(39)(40) and suggested that the decrease of viral genome copies and transcription levels resulted in lowered levels of the E6 and E7 oncoproteins, which causes a reduced proliferation.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This experiment was repeated three times with similar outcomes. These findings are similar to the effects reported by the reduction of E6 and E7 transcript levels in cervical cancer cell lines by siRNA or expression of E2 or E8^E2C proteins (18,(37)(38)(39)(40) and suggested that the decrease of viral genome copies and transcription levels resulted in lowered levels of the E6 and E7 oncoproteins, which causes a reduced proliferation.…”
Section: Resultssupporting
confidence: 77%
“…The pInducer 20-IFN-plasmid was constructed by in vitro recombination of pInducer20 (17) with pENTR4-IFN-. Reporter plasmids pGL18 URR and pGL31 URR have been previously described (18). Expression plasmids for SP100 isoforms and the shSp100 expression construct and the respective control were kindly provided by S. Schreiner and have been previously described (19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…In the E8 KWK mt, E8 residues K5/W6/K7 were changed to AAA, which also changes the E1 coding sequence from E138/V139/E140 to GSG. The pGL 16URR-luc and pC18-Sp1-luc luciferase reporter plasmids and the expression plasmids for HPV16 E2 and HPV16 E8^E2C and the respective hemagglutinin (HA)-tagged versions (HPV16 E2-HA and HPV16 E8^E2C-HA) have been previously described (27). Plasmid pSG 16 E8^E2C KWK mt and 16 E8^E2C-KWK mt -HA were constructed by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analyses have revealed that E8^E2C is a potent inhibitor of the genome replication of HR-HPV16, -18 and -31 in undifferentiated cells (29,30,34,35). HR-HPV E8^E2C proteins are efficient repressors of the major viral early promoter (27,30,34,36,37). In addition, E8^E2C proteins inhibit the E1-and E2-dependent replication of the viral origin (30,34,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation